General Average and Risk Management in Medieval and Early Modern Maritime Business - Fusaro, Maria; Addobbati, Andrea; Piccinno, Luisa (Springer Nature, 2023)
This open access book explores the history of risk management in medieval and early modern European maritime business, focusing particularly on 'General Average' - a mechanism by which extraordinary expenses regarding ship or cargo, incurred during a voyage to save the venture, are shared between all participants to protect equity. This volume traces the history of this risk management tool from its origins in the pre-Roman Mediterranean through to its use in the shipping sector today. Contributions range from the Islamic Mediterranean to the Low Countries, and taken together, provide a wide-ranging analysis of social, cultural, and political aspects of pre-modern maritime commerce in Europe.